Tsuru: el cacao en alta Talamanca - Acuña Sossa, Kathia (2013)
The following article addresses the social and historical process regarding the culture of cocoa in the indigenous communities in Talamanca, stretching from the pre-Hispanic period to present day. This period is separated into socio-historical models, segmented within two historical milestones distinguished by the prominence of a series of social practices. In total, four periods were identified: the first one is marked by tradition, encompassing the pre-Hispanic period until 1908; the second one, by enclave.